Silver-plated material, electrical contact terminal, and production method of silver-plated material

JP2025020701APending Publication Date: 2025-02-13DOWA METALTECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023124227
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

Smart Images

  • Figure 2025020701000001
    Figure 2025020701000001
  • Figure 2025020701000002
    Figure 2025020701000002
  • Figure 2025020701000003
    Figure 2025020701000003
Patent Text Reader

Abstract

To provide a silver-plated material having high Vickers hardness and good contact resistance even after heating, and the production method thereof, and an electrical contact terminal consisting of the silver-plated material.SOLUTION: Provided are a silver-plated material and its related technique, in which a silver plated layer is formed on the surface of a substrate whose surface is at least made of copper or a copper alloy. In the silver plated layer of the silver-plated material, an Sb content is between 0.1 mass% and 1 mass%; an Ag content is 99 mass% or more; an average crystal grain size measured by EBSD is less than 0.2 μm; and Vickers hardness is 105HV or more after 240-hour heating at 200°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silver-plated product, a terminal for electrical contacts, and a method for manufacturing the silver-plated product. [Background technology]

[0002] 2. Description of the Related Art Conventionally, as materials for contacts and terminal parts of connectors, switches and the like, plated materials have been used in which a base material that is relatively inexpensive and has excellent corrosion resistance and mechanical properties, such as copper, copper alloys, or stainless steel, is plated with tin, silver, gold, or the like depending on the required properties, such as electrical properties and solderability.

[0003] Tin-plated products, which are made by plating tin on a substrate such as copper or copper alloy or stainless steel, are inexpensive but have poor corrosion resistance in high-temperature environments. Gold-plated products, which are made by plating gold on these substrates, have excellent corrosion resistance and high reliability, but are expensive. On the other hand, silver-plated products, which are made by plating Ag (silver) on these substrates, are inexpensive compared to gold-plated products and have excellent corrosion resistance compared to tin-plated products.

[0004] However, because silver-plated materials are soft, when used as materials for connection terminals and the like, they are prone to adhesion wear due to insertion / removal and sliding, and there are also problems in that the surface is scraped off when the connection terminal is inserted, increasing the coefficient of friction and requiring a high insertion force.

[0005] To solve such problems, a method is known in which the hardness of a silver-plated product is improved by incorporating an element such as Sb (antimony) into the silver plating (see, for example, Patent Document 1).

[0006] The problem with Patent Document 1 is to provide a high surface hardness, improved wear resistance, and little loss in hardness even in a heated environment, thereby improving heat resistance. The following is described in Table 2 of Patent Document 1.

[0007] When the Sb content in the silver plating layer exceeds 1 mass%, the average crystal grain size is 0.08 to 0.3 μm. In this case, the Ag content in the silver plating layer is less than 99 mass%. In this case, the Vickers hardness after heating (heated at 175°C for 240 hours) is 106 Hv or more. Hereinafter, the unit of hardness may be omitted.

[0008] When the Sb content in the silver plating layer is 1 mass % or less, the average crystal grain size is 0.2 to 3.8 μm. In this case, the Vickers hardness is a maximum of 152, but after heating (heated at 175° C. for 240 hours), the Vickers hardness decreases to 101 or less. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2020-105551 A Summary of the Invention [Problem to be solved by the invention]

[0010] When the silver plating layer contains antimony (Sb) at a high concentration of more than 1 mass %, there is a problem that the contact resistance of the silver plating layer increases.

[0011] On the other hand, when the Sb content is simply reduced as described in Patent Document 1, the hardness is significantly reduced by heating, and there is a problem that the Vickers hardness after heating is low.

[0012] An object of the present invention is to provide a silver-plated product which has high Vickers hardness and good contact resistance even after heating, a method for producing the same, and a terminal for electrical contacts which is made of the silver-plated product. [Means for solving the problem]

[0013] The present inventors first attempted to improve the manufacturing method of the silver-plated product, and as a result, discovered the following combination of configurations. · The silver plating bath is cyanide-based. The Sb concentration in the silver plating bath is mainly set using antimony tartrate. In addition, the term "antimony tartrate" as used herein includes salts of antimony tartrate (e.g., potassium antimonyl tartrate, sodium antimonyl tartrate). Set the Sb concentration to 100-300mg / L. -Add aromatic sulfonate (e.g. sodium naphthalene sulfonate) to the silver plating bath.

[0014] It has been discovered that, by using the silver plating bath having the above composition, as shown in the Examples section below, even if the Sb content in the silver plating layer of the obtained silver-plated product is a small amount of Sb, not less than 0.1% by mass and not more than 1% by mass, it is possible to obtain a plated product that has high Vickers hardness even after heating to 200° C., which is a higher temperature than that in Patent Document 1.

[0015] The aspects of the present invention created based on the above findings are as follows.

[0016] [1] A silver-plated product having a silver plating layer formed on a surface of a substrate having a copper or copper alloy surface, In the silver plating layer, the Sb content is 0.1 mass% or more and 1 mass% or less, the Ag content is 99 mass% or more, and the average crystal grain size as measured by EBSD is less than 0.2 μm, A silver-plated material with a Vickers hardness of 105HV or more after being heated at 200℃ for 240 hours.

[0017] [2] The silver-plated product according to [1], further comprising an underlayer made of nickel between the base material and the silver plating layer.

[0018] [3] The silver-plated product according to [2], wherein the silver plating layer has a thickness of 0.5 μm to 45 μm, and the underlayer has a thickness of 0.5 to 5 μm.

[0019] [4] The silver-plated product according to [1], having a Vickers hardness before heating of 130 Hv or more.

[0020] [5] A terminal for electrical contacts, comprising the silver-plated product according to any one of [1] to [4].

[0021] [6] A method for producing a silver-plated product, comprising forming a silver plating layer on a surface of a substrate made of copper or a copper alloy, the method comprising the steps of: The silver plating layer is formed using a silver plating bath containing silver, cyanide, antimony tartrate, and an aromatic sulfonate; The Sb concentration of the silver plating bath using antimony tartrate is set to 100 to 300 mg / L. A manufacturing method for silver-plated products.

[0022] [7] The method for producing a silver-plated product according to [6], wherein the Ag concentration of the silver plating bath is 30 to 60 g / L.

[0023] [8] The method for producing a silver-plated product according to [6], wherein the free cyanide concentration in the silver plating bath is 75 to 125 g / L.

[0024] [9] The aromatic sulfonate is sodium naphthalene sulfonate, The method for producing a silver-plated product according to [6], wherein the concentration of sodium naphthalenesulfonate in the silver plating bath is 0.1 to 1.5 g / L.

[0025]

[10] The aromatic sulfonate is sodium naphthalene sulfonate, The method for producing a silver-plated product according to [6], wherein the silver plating bath has an Ag concentration of 30 to 60 g / L, a free cyanide concentration of 75 to 125 g / L, and a sodium naphthalenesulfonate concentration of 0.1 to 1.5 g / L. Effect of the Invention

[0026] According to the present invention, there can be provided a silver-plated product which has high Vickers hardness and good contact resistance even after heating, a method for producing the same, and a terminal for electrical contacts which is made of the silver-plated product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The present embodiment will be described below. In this specification, the symbol "to" indicates a value that is equal to or greater than a given value and is equal to or less than a given value.

[0028] [Manufacturing method of silver-plated products] The embodiment of the method for producing a silver-plated product of the present invention is a method for producing a silver-plated product in which a silver plating layer is formed on a substrate by electroplating in a silver plating bath. Each component of the method for producing a silver-plated product will be described below.

[0029] <<Base material>> As the constituent material of the substrate on which the silver plating layer is formed, one that can be silver plated and has the conductivity required for materials such as sliding electrical contact parts such as switches and connectors is suitable. Furthermore, from the viewpoint of cost, Cu (copper) and Cu alloys are suitable as the constituent material of the substrate. As the Cu alloy, from the viewpoint of conductivity and strength, an alloy composed of Cu, at least one selected from the group consisting of Si (silicon), Fe (iron), Mg (magnesium), P (phosphorus), Ni (nickel), Sn (tin), Co (cobalt), Zn (zinc), Be (beryllium), Pb (lead), Te (tellurium), Ag (silver), Zr (zirconium), Cr (chromium), Al (aluminum) and Ti (titanium), and inevitable impurities is preferred. The amount of Cu in the Cu alloy is preferably 85% by mass or more, more preferably 92% by mass or more (the amount of Cu is preferably 99.95% by mass or less).

[0030] As described below, the substrate is preferably used for terminal applications (as a silver-plated material on which a silver plating layer is formed), but the substrate itself may have a shape for such applications, or the substrate may have a flat shape (such as a flat plate shape) and be formed into the shape for application after becoming a silver-plated material.

[0031] << Formation of base layer >> In the method for producing a silver-plated product of the present invention, a base layer may be formed on the substrate, and the base layer may be electroplated as described below. The base layer is formed for the purpose of preventing copper of the substrate from diffusing to the plating surface and oxidizing, which deteriorates the electrical conductivity of the silver-plated product, and for the purpose of improving the adhesion of the silver-plated layer. The constituent metal of the base layer may be at least one metal or alloy selected from the group consisting of Cu, Ni, Sn, and Ag. The base layer may be a single layer of Cu, Ni, Sn, Ag, or an alloy thereof, or a layer of a combination of these (laminate structure), and the base layer may be formed on the entire surface layer of the substrate or a part of it depending on the application of the silver-plated product to be produced.

[0032] For example, in order to prevent copper in the base material from diffusing to the surface of the silver plating layer and thereby deteriorating the electrical conductivity, it is preferable to form an underlayer made of Ni. In this specification, Ni plating is exemplified as the underlayer.

[0033] Incidentally, when the substrate is a copper alloy containing zinc, such as brass, it is preferable to form an undercoat layer made of Cu in order to prevent the zinc in the substrate from diffusing onto the surface of the silver plating layer.

[0034] For the purpose of improving the adhesion of the silver plating layer to the substrate, it is preferable to form an underlayer made of Ag.

[0035] The thickness of the underlayer is not particularly limited, but from the viewpoints of function and cost, it is preferably 0.5 to 5.0 μm, more preferably 0.5 to 4.0 μm, and even more preferably 0.5 to 3.0 μm.

[0036] The method for forming the underlayer is not particularly limited, and it can be formed by electroplating using a plating bath containing the above-mentioned constituent metals by a known method, or by stacking layers made of each metal that constitutes the desired alloy layer in order and then reflowing (heat treating).

[0037] <<Agストライクめっき> > Before forming a silver plating layer on the substrate, it is preferable to form a very thin intermediate layer by Ag strike plating to improve the adhesion between the substrate and the silver plating layer. When a base layer is formed on the substrate, Ag strike plating is performed on the base layer (thereby improving the adhesion between the base layer and the silver plating layer). As a method for implementing Ag strike plating, any conventionally known method can be adopted without particular limitation as long as it does not impair the effects of the present invention.

[0038] <<Electroplating>> In the method for producing a silver-plated product of the present invention, the base material described above is subjected to electroplating in a specific silver plating bath, after which an underlayer and / or an intermediate layer is formed by Ag strike plating as necessary, thereby forming a silver plating layer on the base material.

[0039] <Silver plating bath> The silver plating bath contains silver and has the following composition. The silver plating bath is a cyanide-based bath. In other words, the silver plating bath contains cyanide (e.g., free cyanide). In this specification, "cyan" is a general term for substances that contain cyanide ions. The Sb concentration in the silver plating bath is mainly set using antimony tartrate. Set the Sb concentration in the silver plating bath to 100 to 300 mg / L. -Add aromatic sulfonate (e.g. sodium naphthalene sulfonate) to the silver plating bath. That is, the silver plating bath contains silver, cyanide, antimony tartrate, and an aromatic sulfonate. In this specification, the following sodium naphthalenesulfonate is exemplified as sodium 1-naphthalenesulfonate. [ka] However, the use of sodium 2-naphthalenesulfonate is not precluded. Also, sodium naphthalenesulfonate is an example of an aromatic sulfonate, and the use of other compounds that are aromatic sulfonates is not precluded. For example, sodium benzenemonosulfonate, sodium benzene 1,3-disulfonate, sodium naphthalene 1,5-, 2,6-, 2,7-disulfonate, and sodium naphthalene 1,3,5-trisulfonate are included.

[0040] There is no limitation on the specific composition of the silver plating bath as long as it has the above-mentioned configuration. As an example of a specific composition, the silver plating bath may be a cyanide-based aqueous solution containing potassium silver cyanide (KAg(CN)2), potassium cyanide (KCN), and potassium selenocyanate (KSeCN). This silver plating bath may also contain potassium carbonate (K2CO3).

[0041] The silver plating bath may have an Ag concentration of 30 to 60 g / L, and the concentration of potassium silver cyanide, which is the basis of the Ag concentration, may be 55 to 110 g / L.

[0042] The free cyanide concentration in the silver plating bath may be 75 to 125 g / L. In this specification, the concentration of potassium cyanide other than potassium silver cyanide is considered to be the free cyanide concentration.

[0043] The concentration of sodium naphthalenesulfonate in the silver plating bath may be 0.1 to 1.5 g / L.

[0044] It is preferable to use only antimony tartrate (for example, only potassium antimonyl tartrate) as the Sb source when setting the Sb concentration to 100 to 300 mg / L, but it is permissible to contain a small amount of an Sb source other than antimony tartrate as long as it does not inhibit the effect of antimony tartrate. For example, if the Sb concentration can be set to 100 to 300 mg / L using only antimony tartrate and the Sb concentration in the final silver plating bath is within 100 to 300 mg / L, the proportion of antimony tartrate in the Sb source may be 85 mass% or more.

[0045] Although the inclusion of selenium in the silver plating bath is not excluded, it is preferable that the amount of selenium is at least less than 10 mass% relative to the mass of antimony in the silver plating bath, and from the viewpoint of waste liquid treatment, it is preferable that the amount of selenium is substantially zero (the lower measurement limit, for example, 1 ppm or less).

[0046] The Ag concentration in the silver plating bath may be 5 to 150 g / L, 10 to 120 g / L, or 20 to 100 g / L.

[0047] In any case, when electroplating is performed using the silver plating bath according to the present embodiment, the Vickers hardness of the silver-plated product after heating is high, and at the same time, when electroplating is performed using the silver plating bath according to the present embodiment, the contact resistance of the silver-plated product after heating is also kept low.

[0048] Moreover, as shown in the Examples section below, it was found that even with varying Sb concentrations of 260 mg / L (Example 1), 140 mg / L (Example 2), and 200 mg / L (Example 3) within the range of 100 to 300 mg / L, the Vickers hardness after heating resulted in a small variation of approximately 105 to 115. The same is true for the contact resistance after heating. These results show that good products can be stably provided even if the Sb concentration varies to some extent during the production of silver-plated products. This is a very advantageous effect in the production of silver-plated products.

[0049] The same can be said about potassium cyanide concentration (KCN concentration, Free Cyan concentration in this specification). As shown in the Examples section below, it was found that even when the KCN concentration was varied within the range of 75 to 125 mg / L, such as 125 mg / L (Example 1), 75 mg / L (Example 2), and 100 mg / L (Example 3), the Vickers hardness after heating was found to have a small variation of about 105 to 115.

[0050] In addition, Example 3 and Comparative Example 1 in the Examples section below are examples in which the only difference is whether or not sodium naphthalenesulfonate is included in the silver plating bath, but by including sodium naphthalenesulfonate, the Vickers hardness before and after heating is improved. It has been found that sodium naphthalenesulfonate not only contributes to improving the Vickers hardness after heating and the contact resistance after heating, which is the effect of the present invention described above, but also has the effect of raising the Vickers hardness before and after heating.

[0051] As other additives, for example, the silver plating bath used in the present invention may further contain known additives (e.g., hardeners, conductive salts, etc.).

[0052] The solvent constituting the silver plating bath is mainly water. Water is preferred because of its solubility in silver and other components contained in the plating bath, and its low environmental impact. A mixed solvent of water and alcohol may also be used as the solvent.

[0053] <Electroplating conditions> Next, various conditions for electroplating using the above-described silver plating bath will be described.

[0054] (Cathode and Anode) The substrate to be electroplated is the cathode. The anode is the silver electrode plate, for example, that dissolves to provide silver.

[0055] (current density) The cathode and anode are immersed in a silver plating bath (plating bath) and a current is passed through them to perform silver plating. The current density here is set to 0.5 to 10 A / dm from the viewpoint of the speed at which the silver plating layer is formed and from the viewpoint of suppressing unevenness in the appearance of the silver plating layer. 2 is preferable, and 1 to 8 A / dm 2 More preferably, 1 to 5 A / dm 2 is more preferred.

[0056] (Temperature, stirring, plating time, plating area) The temperature of the plating bath (silver plating bath) during electroplating (plating temperature) is preferably 15 to 50°C, more preferably 20 to 45°C, from the viewpoints of plating production efficiency and preventing excessive evaporation of the solution.

[0057] In this case, the stirring speed of the plating bath with a stirrer or stirring blade is preferably 300 to 700 rpm, and more preferably 350 to 650 rpm, from the viewpoint of carrying out uniform plating.

[0058] The silver plating time (time for applying electric current) can be adjusted appropriately depending on the desired thickness of the silver plating layer, but is typically in the range of 25 to 1800 seconds.

[0059] The area to be plated may be the entire surface layer of the substrate or a part of the surface layer of the substrate, depending on the application of the silver-plated product to be manufactured.

[0060] [Silver-plated material] Hereinafter, an embodiment of the silver-plated product of the present invention will be described. The silver-plated product according to this embodiment can be manufactured, for example, by the method for manufacturing a silver-plated product according to this embodiment. Each component of this silver-plated product will be described below. However, descriptions that overlap with the above [Method for manufacturing a silver-plated product] will be omitted as appropriate.

[0061] The silver-plated product according to this embodiment is a silver-plated product in which a silver plating layer is formed on the surface of a base material having at least the surface made of copper or a copper alloy. In the silver plating layer, the Sb content is 0.1 mass% or more and 1 mass% or less, and the Ag content is 99 mass% or more. In the silver plating layer, the average crystal grain size measured by EBSD is less than 0.2 μm. The Vickers hardness after heating at 200℃ for 240 hours (the Vickers hardness after heating discussed above) is 105HV or more.

[0062] As described above as the findings of the present invention, in the silver-plated product according to this embodiment, even if the Sb content is a small amount of Sb, such as 0.1 mass % or more and 1 mass % or less, the effect of improving the Vickers hardness after heating is sufficiently exhibited.

[0063] In this case, in the silver-plated layer of the silver-plated product according to this embodiment, the average crystal grain size as measured by EBSD is less than 0.2 μm, preferably 0.15 μm or less, and more preferably 0.13 μm or less.

[0064] As mentioned above, in Table 2 of Patent Document 1, when the Sb content in the silver plating layer is 1 mass % or less, the particle size before heating is 0.2 to 3.8 μm.

[0065] On the other hand, even though the Sb content in the silver-plated layer of the silver-plated product according to this embodiment is also 1 mass % or less, the average crystal grain size measured by EBSD measurement (details will be described later in the Examples section) is less than 0.2 μm. Nevertheless, in the silver-plated product according to this embodiment, the Vickers hardness after heating is 105 or more (101 or less in Table 2 of Patent Document 1), and the contact resistance after heating is also good.

[0066] <<Base material>> The substrate in the silver-plated product according to this embodiment is the same as the substrate described above in relation to the method for producing a silver-plated product of the present invention.

[0067] <<Underlayer>> An underlayer may be formed between the substrate and the silver plating layer for various purposes. The constituent metal of the underlayer may be at least one metal or alloy selected from the group consisting of Cu, Ni, Sn, and Ag.

[0068] <<Silver plating layer>> The silver plating layer formed on the base material is composed of a silver layer. When Ag strike plating is performed before forming the silver plating layer, an intermediate layer due to this strike plating exists between the base material (or the underlayer described later) and the silver plating layer, but it is often very thin and indistinguishable from the silver plating layer. Also, the silver plating layer may be formed over the entire surface layer of the base material or on a part of the surface layer.

[0069] As described above, in the silver plating layer, the Sb content is 0.1% by mass or more and 1% by mass or less, the Ag content is 99% by mass or more, and the average crystal grain size by EBSD measurement in the silver plating layer is less than 0.2 μm.

[0070] <Content> The Ag content in the silver plating layer of the silver plating material according to the present embodiment is 99% by mass or more (specifically 99.0% by mass or more), and the Sb content is 0.1% by mass or more and 1% by mass or less. The lower limit of the Sb content may be 0.2% by mass or more, 0.3% by mass or more, 0.4% by mass or more, or 0.5% by mass or more. The upper limit of the Sb content may be 0.9% by mass or less. The Se (selenium) content is preferably at the measurement lower limit, for example, 1 ppm or less. Details of the measurement method of the content of each composition in the silver plating layer of the silver plating material will be described in the examples section.

[0071] <Average crystal grain size by EBSD measurement> As described above, when EBSD measurement is performed on the particles in the silver plating layer of the silver plating material according to the present embodiment, the measurement result is less than 0.2 μm. Alternatively, it may be 0.15 μm or less, 0.13 μm or less. There is no limitation on the lower limit, but it may be, for example, 0.08 μm or more. Details of the measurement method of the average crystal grain size by EBSD measurement will be described in the examples section.

[0072] <Vickers hardness> As described above, the Vickers hardness after heating of the silver plating material according to the present embodiment is 105 or more. The Vickers hardness before heating is not limited, but is preferably at least 130, and more preferably at least 155. The upper limit of the Vickers hardness before and after heating is not limited, but is, for example, 300 or less. In addition, the value of "(Vickers hardness after heating - Vickers hardness before heating) / Vickers hardness before heating" may be -0.40 or more, or -0.35 or more. There is no upper limit, but it is, for example, 0.10 or less or less than 0. The method for measuring the Vickers hardness Hv will be described in detail in the Examples section.

[0073] <Contact resistance> As described above, the contact resistance after heating of the silver-plated product according to this embodiment is good. The method for measuring the contact resistance before and after heating is based on JCBA T323 "Method for measuring surface contact electrical resistance." For example, evaluation is performed with no sliding and with a sliding speed of 1 mm / min. The smaller the contact resistance, the better, and the smaller the change in contact resistance before and after heating, the better.

[0074] Specifically, the contact resistance before heating, measured by the method (four-terminal method) described in the Examples section below, is preferably 1.50 mΩ or less at a load of 50 gf and 0.70 mΩ or less at a load of 100 gf in a non-sliding state. The contact resistance before heating is preferably 0.70 mΩ or less at a load of 50 gf when sliding at a sliding speed of 1 mm / min and a sliding distance of 0.5 mm, and is preferably 0.60 mΩ or less at a load of 100 gf when sliding at a sliding speed of 1 mm / min and a sliding distance of 1.0 mm. There is no lower limit to the contact resistance before heating, but it is, for example, 0.10 mΩ or more.

[0075] The contact resistance after heating is preferably 2.70 mΩ or less at a load of 50 gf and 2.00 mΩ or less at a load of 100 gf in a non-sliding state. In the post-heating contact resistance, the contact resistance at a load of 50 gf when sliding at a sliding speed of 1 mm / min and a sliding distance of 0.5 mm is preferably 0.60 mΩ or less, and the contact resistance at a load of 100 gf when sliding at a sliding speed of 1 mm / min and a sliding distance of 1.0 mm is preferably 0.40 mΩ or less. There is no lower limit for the pre-heating contact resistance, but it is, for example, 0.10 mΩ or more.

[0076] The method for measuring the contact resistance will be described in detail in the Examples section.

[0077] <Thickness of silver plating layer> The thickness of the silver plating layer is not particularly limited, but it is preferable that there is a minimum thickness in terms of wear resistance, reliability, and conductivity. If the thickness is too large, the effect of the silver plating layer is saturated and the raw material cost increases. From the above viewpoints, the thickness of the silver plating layer is preferably 0.5 to 45 μm, more preferably 1 to 35 μm, and even more preferably 1.5 to 25 μm. The thickness of the silver plating layer can be measured with a fluorescent X-ray film thickness meter, and details of the measurement method will be given in the section of Examples.

[0078] [Terminal] The silver-plated product according to this embodiment is suitable as a constituent material for terminals for electrical contacts, particularly terminals in electrical contact parts such as switches and connectors that undergo sliding during use. EXAMPLES

[0079] EXAMPLES Hereinafter, examples of the silver-plated product and the manufacturing method thereof according to the present invention will be described in detail.

[0080] [Example 1] <Substrate and pretreatment for substrate> A rolled plate made of oxygen-free copper (C1020 1 / 2H) measuring 67mm x 50mm x 0.3mm was prepared as the substrate, and this rolled plate was used as the material to be plated. As a pretreatment for this material to be plated, the material to be plated and the SUS plate were placed in an alkaline degreasing solution, and electrolytic degreasing was performed for 30 seconds at a voltage of 5V with the material to be plated as the cathode and the SUS plate as the anode, followed by rinsing with water and pickling in 3% sulfuric acid for 15 seconds.

[0081] <Formation of the base layer> In a matte nickel plating solution consisting of an aqueous solution containing 540 g / L nickel sulfamate tetrahydrate, 25 g / L nickel chloride, and 35 g / L boric acid, the pretreated workpiece was used as the cathode and the nickel electrode plate was used as the anode, and the solution was stirred at 500 rpm with a stirrer at a liquid temperature of 50°C and a current density of 5 A / dm 2 The thickness of the central portion of the matte nickel plating film was measured with a fluorescent X-ray film thickness gauge (SFT-110A manufactured by Hitachi High-Tech Science Co., Ltd.) to be 1 μm.

[0082] <Agストライクめっき> In an Ag strike plating solution consisting of an aqueous solution containing 3 g / L of potassium silver cyanide (KAg(CN)2) and 90 g / L of potassium cyanide (KCN), the workpiece with a base plating film was used as the cathode, and a platinum-coated titanium electrode plate was used as the anode. The workpiece was stirred at 500 rpm with a stirrer at room temperature (25°C) with a current density of 2.0 A / dm 2 for 10 seconds to form an Ag strike plating film, and then the silver strike plating solution was thoroughly washed away by rinsing with water.

[0083] <Silver plating> An aqueous silver plating solution composed of 74.1 g / L of potassium silver cyanide (KAg(CN)₂, equivalent to 40 g / L in terms of Ag concentration), 125 g / L of potassium cyanide (KCN), potassium antimonyl tartrate (antimony concentration 260 mg / L), and 0.3 g / L of sodium naphthalenesulfonate as a brightener. In this solution, a plated material with a silver strike plating film formed on it was used as the cathode, and a silver electrode plate was used as the anode. While stirring at 500 rpm with a stirrer, electroplating was carried out at a liquid temperature of 30 °C to form a silver plating film. At this time, the current density was 3 A / dm 2 , and the plating time was 200 seconds. The film thickness was measured by a fluorescent X-ray film thickness gauge (SFT-110A manufactured by Hitachi High-Technologies Corporation) at the center of the silver plating film, and the film thickness was about 5 μm.

[0084] The following evaluations were performed on the obtained silver-plated materials.

[0085] <Content> Cut out the plated material, add pure water and nitric acid, and heat and dissolve it at 150 °C for 30 minutes. Then, add hydrochloric acid to precipitate silver chloride, and perform heat aging of silver chloride at 150 °C for 30 minutes. Then, perform filtration and separate it into the filtrate and silver chloride. The antimony concentration is determined by ICP measurement of the filtrate. The silver concentration is determined by a gravimetric method using silver chloride. As a result, the Ag content in the silver plating layer of Example 1 was 99.1 mass%, and the Sb content was 0.9 mass%. In addition, except for Comparative Examples 3, 4, and 5 described later, Se was not detected from the silver plating layer (Se was 1 ppm or less).

[0086] <Average crystal grain size by EBSD measurement> The average crystal grain size of the silver plating layer was measured from the results of EBSD (Electron Backscatter Diffraction Pattern) analysis of the cross section. The cross section perpendicular to the rolling direction was observed, and the average crystal grain size and standard deviation were measured. Specifically, the cross section was exposed using a cross-section polisher, and the plated portion was observed with an FE-SEM (JSM-7200F manufactured by JEOL Ltd.) to determine the measurement area.

[0087] Then, using an EBSD measurement device (Symmetry, manufactured by Oxford Instruments) and EBSD data analysis software (OIM-Analysis 7.3.1, manufactured by TSL Solutions Co., Ltd.), the orientation difference of each crystal grain was analyzed over a measurement area of ​​25.0 μm x 8.0 μm with an electron beam acceleration voltage of 20 kV and measurement intervals of 0.02 μm steps.

[0088] The CI (Confidence Index) value of each measurement point was calculated using analysis software, and those with a CI value of 0.1 or less were excluded from the analysis of grain size.

[0089] Grain boundaries were determined by observing two-dimensional cross sections, and a grain boundary map was created by excluding twin crystals from measurement points where the difference in orientation between two adjacent crystals was 15° or more.

[0090] The crystal grain size was measured by calculating the average crystal grain size by the area fraction method.

[0091] The average crystal grain size in the silver plating layer in Example 1 was 0.10 μm.

[0092] <Vickers hardness> The Vickers hardness Hv of the surface of the silver plating layer of the silver-plated product was measured in accordance with JIS Z 2244 using a microhardness tester (HM221 manufactured by Mitutoyo Corporation) by applying a load of 10 gf to the silver-plated product for 10 seconds, and the average value of three measurements was used.

[0093] The Vickers hardness before heating was measured as described above. The Vickers hardness after heating was measured as described above for silver-plated materials stored in air at 200°C for 240 hours.

[0094] In Example 1, the Vickers hardness before heating was 173.1, and the Vickers hardness after heating was 115.5.

[0095] The manufacturing conditions of the above silver-plated products are summarized in Table 1, along with the manufacturing conditions of Examples 2 to 3 and Comparative Examples 1 to 5 described below. In the table, sodium naphthalenesulfonate is represented as α. Details of the silver-plated products obtained under the above manufacturing conditions are summarized in Table 2, along with details of Examples 2 and 3 and Comparative Examples 1 to 5 described below. Strictly speaking, the Vickers hardness was measured on the silver-plated products, but since it is the silver-plated layer that the contactor actually comes into contact with, Table 2 lists the Vickers hardness as the hardness on the silver-plated layer. [Table 1] [Table 2]

[0096] [Example 2] A silver-plated material was prepared in the same manner as in Example 1, except that in the <silver plating> of Example 1, the concentration of potassium cyanide (KCN) was changed to 75 g / L and the antimony concentration of potassium antimonyl tartrate was changed to 140 mg / L.

[0097] The silver plating layer in Example 2 had an Ag content of 99.5 mass % and an Sb content of 0.5 mass %. The average crystal grain size in the silver plating layer in Example 2 was 0.11 μm. In Example 2, the Vickers hardness before heating was 157.4, and the Vickers hardness after heating was 105.5.

[0098] <Contact resistance> Using an electrical contact simulator (CRS-1 manufactured by Yamazaki Seiki Kenkyusho) conforming to JCBA T323, a probe (contact type: Au) was pressed against the silver-plated sheet material to measure the contact resistance. Measurements were performed under four different maximum load and sliding conditions. When the probe contacted the silver-plated material, the load was zero, and from there, the load on the probe was increased with the probe remaining in the same position (no sliding) or sliding at a sliding speed of 1 mm / min (sliding), and the resistance value at the maximum load was measured. The applied current during resistance measurement was 10 mA. The measurement results are the average of three measurements. Condition 1: No sliding, maximum load 50gf after 0.5 minutes from 0 load Condition 2: No sliding, maximum load 100gf after 1.0 minute from load 0 Condition 3: With sliding, maximum load 50gf 0.5 minutes after load 0, sliding distance 0.5mm Condition 4: With sliding, maximum load 100gf after 1.0 minute from load 0, sliding distance 1.0mm

[0099] For each measurement with and without sliding, the silver-plated material was stored in air at 120°C for 240 hours and then measured as described in the above paragraph.

[0100] The contact resistance values ​​in Example 2 were as follows: Before heating and under condition 1 (no sliding, 50gf): 1.18mΩ After heating and under condition 1 (no sliding, 50gf): 1.89mΩ Before heating and condition 2 (no sliding, 100gf): 0.46mΩ After heating and condition 2 (no sliding, 100gf): 0.77mΩ Before heating and under condition 3 (with sliding, 50gf): 0.53mΩ After heating and under condition 3 (with sliding, 50gf): 0.31mΩ Before heating and condition 4 (with sliding, 100gf): 0.25mΩ After heating and condition 4 (with sliding, 100gf): 0.22mΩ

[0101] The contact resistance values ​​of the silver-plated products according to Examples 2 and 3 and Comparative Example 2 are summarized in Table 3. Strictly speaking, the contact resistance was measured on the silver-plated products, but since it is the silver plating layer that the contactor actually comes into contact with, Table 3 states that the contact resistance is relative to the silver plating layer. [Table 3]

[0102] [Example 3] A silver-plated material was prepared in the same manner as in Example 1, except that in the <silver plating> of Example 1, the concentration of potassium cyanide (KCN) was changed to 100 g / L and the antimony concentration of potassium antimonyl tartrate was changed to 200 mg / L.

[0103] The silver plating layer in Example 3 had an Ag content of 99.3 mass % and an Sb content of 0.7 mass %. The average crystal grain size in the silver plating layer in Example 3 was 0.10 μm. In Example 3, the Vickers hardness before heating was 166.0, and the Vickers hardness after heating was 110.8.

[0104] The contact resistance values ​​in Example 3 were as follows: Before heating and under condition 1 (no sliding, 50gf): 1.20mΩ After heating and under condition 1 (no sliding, 50gf): 2.45mΩ Before heating and condition 2 (no sliding, 100gf): 0.45mΩ After heating and condition 2 (no sliding, 100gf): 1.77mΩ Before heating and under condition 3 (with sliding, 50gf): 0.41mΩ After heating and under condition 3 (with sliding, 50gf): 0.47mΩ Before heating and condition 4 (with sliding, 100gf): 0.30mΩ After heating and condition 4 (with sliding, 100gf): 0.30mΩ

[0105] [Comparative Example 1] A silver-plated material was prepared in the same manner as in Example 3, except that in the <silver plating> of Example 1, sodium naphthalenesulfonate was not added to the silver plating bath.

[0106] The silver plating layer of Comparative Example 1 had an Ag content of 99.3 mass % and an Sb content of 0.7 mass %. In Example 3, the Vickers hardness before heating was 148.4, and the Vickers hardness after heating was 88.9.

[0107] [Comparative Example 2] A silver-plated product was prepared in the same manner as in Example 1, except that in the <silver plating> of Example 1, the antimony concentration of the potassium antimonyl tartrate was changed to 420 mg / L.

[0108] The silver plating layer of Comparative Example 2 had an Ag content of 98.7 mass % and an Sb content of 1.3 mass %. In Comparative Example 2, the Vickers hardness before heating was 163.0, and the Vickers hardness after heating was 113.7.

[0109] The contact resistance values ​​in Comparative Example 2 were as follows: Before heating and under condition 1 (no sliding, 50gf): 1.16mΩ After heating and under condition 1 (no sliding, 50gf): 12.68mΩ Before heating and condition 2 (no sliding, 100gf): 0.38mΩ After heating and condition 2 (no sliding, 100gf): 14.86mΩ Before heating and under condition 3 (with sliding, 50gf): 0.52mΩ After heating and under condition 3 (with sliding, 50gf): 1.52mΩ Before heating and condition 4 (with sliding, 100gf): 0.50mΩ After heating and condition 4 (with sliding, 100gf): 0.62mΩ

[0110] [Comparative Example 3] Regarding the silver plating bath in <Silver Plating> of Example 1, a silver-plated material was prepared in the same manner as in Example 1, except for the following.

[0111] A silver plating bath was used, consisting of an aqueous solution containing 129 g / L potassium silver cyanide (KAg(CN)2) (equivalent to an Ag concentration of 69 g / L), 140 g / L potassium cyanide (KCN), potassium antimonyl tartrate (antimony concentration 156 mg / L), and potassium selenocyanate (selenium concentration 152 mg / L).

[0112] In the silver plating bath, the plated material on which the silver strike plating film was formed was used as the cathode, and the silver electrode plate was used as the anode. Electroplating was performed at a liquid temperature of 25°C while stirring with a stirrer at 500 rpm to form a silver plating film. At this time, the current density was 12 A / dm 2 The plating time was 53 seconds.

[0113] The thickness of the silver plating layer was measured at the center of the silver plating film using a fluorescent X-ray thickness meter (SFT-110A manufactured by Hitachi High-Tech Science Corporation), and was found to be approximately 5 μm.

[0114] In Comparative Example 3, the Vickers hardness before heating was 131.6, and the Vickers hardness after heating was 97.3.

[0115] [Comparative Example 4] Regarding the silver plating bath in <Silver Plating> of Example 1, a silver-plated material was prepared in the same manner as in Example 1, except for the following.

[0116] A silver plating bath was used, consisting of an aqueous solution containing 175 g / L potassium silver cyanide (KAg(CN)2) (equivalent to 94 g / L in Ag concentration), 95 g / L potassium cyanide (KCN), and potassium selenocyanate (selenium concentration 6 mg / L).

[0117] In the silver plating bath, the workpiece on which the silver strike plating film was formed was used as the cathode, and the silver electrode plate was used as the anode. Electroplating was performed at a liquid temperature of 18°C ​​while stirring with a stirrer at 500 rpm to form a silver plating film. At this time, the current density was 5 A / dm 2 The plating time was 125 seconds.

[0118] The thickness of the silver plating layer was measured at the center of the silver plating film using a fluorescent X-ray thickness meter (SFT-110A manufactured by Hitachi High-Tech Science Corporation), and was found to be approximately 5 μm.

[0119] The Ag content in the silver plating layer of Comparative Example 4 exceeded 99 mass %. In Comparative Example 4, the Vickers hardness before heating was 82.4, and the Vickers hardness after heating was 75.1.

[0120] [Comparative Example 5] A silver-plated product was prepared in the same manner as in Comparative Example 4, except that in the <silver plating> of Comparative Example 4, the selenium concentration of the potassium selenocyanate was changed to 70 mg / L.

[0121] The Ag content in the silver plating layer of Comparative Example 5 exceeded 99 mass %. In Comparative Example 5, the Vickers hardness before heating was 133.8, and the Vickers hardness after heating was 89.2.

[0122] [result] According to each example, it was found that even if the Sb content in the silver plating layer of the obtained silver-plated product is a small amount of Sb, such as 0.1 mass % or more and 1 mass % or less, the effect of improving the Vickers hardness after heating is sufficiently exerted.

[0123] In addition, when comparing Comparative Example 2 (Sb content in the silver plating layer exceeding 1 mass%) with Examples 2 and 3 (Sb content in the silver plating layer ranging from 0.1 mass% to 1 mass%), it was found that the contact resistance after heating was greatly improved.

Claims

1. A silver-plated product having a silver plating layer formed on a surface of a substrate having a copper or copper alloy surface, The silver plating layer has an Sb content of 0.1 mass % or more and 1.0 mass % or less, an Ag content of 99 mass % or more, and an average crystal grain size measured by EBSD measurement of less than 0.2 μm; A silver-plated product having a Vickers hardness of 105 HV or more after being heated at 200°C for 240 hours.

2. The silver-plated product according to claim 1 , further comprising an underlayer made of nickel between the substrate and the silver plating layer.

3. 3. The silver-plated product according to claim 2, wherein the thickness of the silver plating layer is from 0.5 μm to 45 μm, and the thickness of the underlayer is from 0.5 to 5 μm.

4. 2. The silver-plated product according to claim 1, which has a Vickers hardness of 130 Hv or more before being heated at 200° C. for 240 hours.

5. A terminal for electrical contacts, comprising the silver-plated product according to any one of claims 1 to 4.

6. A method for producing a silver-plated product, comprising forming a silver plating layer on a surface of a substrate made of copper or a copper alloy, the method comprising the steps of: The silver plating layer is formed using a silver plating bath containing silver, cyanide, antimony tartrate, and an aromatic sulfonate; The method for producing a silver-plated product comprises adjusting the Sb concentration in the silver plating bath using antimony tartrate to 100 to 300 mg / L.

7. The method for producing a silver-plated product according to claim 6, wherein the Ag concentration of the silver plating bath is 30 to 60 g / L.

8. 7. The method for producing a silver-plated product according to claim 6, wherein the free cyanide concentration in the silver plating bath is 75 to 125 g / L.

9. The aromatic sulfonate is sodium naphthalene sulfonate, The method for producing a silver-plated product according to claim 6, wherein the concentration of sodium naphthalenesulfonate in the silver plating bath is 0.1 to 1.5 g / L.

10. The aromatic sulfonate is sodium naphthalene sulfonate, 7. The method for producing a silver-plated product according to claim 6, wherein the silver plating bath has an Ag concentration of 30 to 60 g / L, a free cyan concentration of 75 to 125 g / L, and a sodium naphthalenesulfonate concentration of 0.1 to 1.5 g / L.

Citation Information

Patent Citations

  • Terminal material for connector

    JP2020105551A